Hallazgo del género trigonobalanus forman, 1962 (fagaceae) en el neotrópico – i (1979)
A new species of Trigonobalanus is described from the clouded sub-Andean forest of the Upper Magdalena Valley in the Cueva de los Guacharos National Park, Colombia. The genus was previously known living today in Indonesia (Celebes), the Malayan Federation (Malaya, Sarawakand Sabah) and Thailand. The characters of the genus are extensively discussed in the light of the new findings and the classification proposed by Forman (1964) for the Fagaceae is accepted, except by the recognition of a new subfamily.